Halal tourism regulations in Indonesia: trends and dynamics in the digital era - Lukman Santoso; Agus Triyanta; Jawahir Thontowi (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
The halal tourism industry is an emerging sector that has recently become a global trend in economic development in many countries. However, in various regions in Indonesia, halal tourism triggers anomalies and raises pros and cons. This article aims to explore the construction of halal tourism development in five regions in Indonesia. It seeks to formulate a sustainable halal tourism regulatory model that is based on plurality and local wisdoms of the local community. This study uses a legal research method, with a critical-constructive approach. The findings from this study conclude that the development of halal tourism regulations in various regions shows a positive and dynamic direction in line with the configuration of regional tourism policies, which needs to be continuously encouraged and accelerated. As such, amid these positive trends and dynamics, regional halal tourism development needs to adopt a sustainable halal tourism regulatory model that is based on community plurality and is responsive to local wisdoms. This article supports the realization of a sustainable halal tourism policy following the Covid-19 pandemic in the midst of a plurality of regional communities.